Managerial Accounting - Le, Van Lien (Khoa Quốc tế, ĐHQGHN, 2020)
This module provides students with an overview of managerial accounting in the organizations ranging from the basic concepts to a variety of managerial accounting techniques. Moreover, the module allows students to evaluate and be able to choose appropriate managerial techniques in a certain context.